2021
DOI: 10.3389/fimmu.2021.670642
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Human Epididymis Protein 4 Is Associated With Disease Activity and Systemic Involvements in Primary Sjögren’s Syndrome

Abstract: BackgroundWe aimed to investigate the clinical utility of human epididymis protein 4, a tumor biomarker being widely utilized in clinical practice in the diagnosis of ovarian cancer, in primary Sjögren’s Syndrome (pSS).MethodsA total of 109 pSS patients and 113 healthy controls (HCs) were included in the study. HE4 were determined by Roche Cobas E601 electrochemical luminescence analyzer. Clinical and laboratory findings were reviewed, and the relationships between HE4 and clinical parameters were determined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Further, high levels of HE4 can stratify patients into SSc-ILD subsets (10). We also showed that HE4 can identify primary Sjögren's syndrome (pSS) patients at risk of pulmonary/renal involvements (11). Taken together, these…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Further, high levels of HE4 can stratify patients into SSc-ILD subsets (10). We also showed that HE4 can identify primary Sjögren's syndrome (pSS) patients at risk of pulmonary/renal involvements (11). Taken together, these…”
Section: Introductionmentioning
confidence: 62%
“…Human epididymis protein 4 has been widely utilized as an effective biomarker in the diagnosis and follow-up of patients with ovarian cancer. Of interest, accumulating evidence suggest that HE4 may also has diagnostic potential in other clinical settings, including lung adenocarcinomas ( 17 ), renal fibrosis ( 18 ), cystic fibrosis ( 19 ), as well as autoimmune-related organ involvements, such as SSc-ILD ( 10 ) and pSS-related pulmonary/renal involvements ( 11 ). In this study, we extended the clinical application of HE4 into the diagnosis of RA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HE4 is a widely used and high-value biomarker for diverse neoplastic diseases, and recent reports indicate that elevated HE4 levels occur in a variety of autoimmune diseases, including SLE, 11 RA 13 and pSS. 12 Available evidence also indicates that it is closely related to concurrent interstitial lung disease and renal involvement. As IgG4-RD is an immune-mediated fibroinflammatory disease, 21 we hypothesised that HE4 might be a potential biomarker for IgG4-RD and evaluated its utility.…”
Section: Discussionmentioning
confidence: 99%
“…Congruently, HE4 was found to be elevated in some autoimmune diseases, including systemic lupus erythematosus (SLE), primary Sjögren’s syndrome (pSS) and rheumatoid arthritis (RA), and notably, this increase was greater in patients with SLE with lupus nephritis 11 patients with pSS and patients with RA with interstitial lung disease. 12 13 HE4 has also been recently recognised as a biomarker for fibrotic disease and is reportedly involved in the aetiopathology of fibrotic diseases because fibroblast-derived HE4 has protease inhibitor activity that can promote the aggregation of collagen and cause fibrosis. 14 15 Based on these observations, and the fact that IgG4-RD is a recognised immune-mediated fibroinflammatory disease, we hypothesised that HE4 may play a role in IgG4-RD fibrosis and that it may be a potential biomarker for this disease.…”
Section: Introductionmentioning
confidence: 99%